Jets in the magnetosheath: IMF control of where they occur - Laura Vuorinen; Heli Hietala; Ferdinand Plaschke (COPERNICUS GESELLSCHAFT MBH, 2025)
Magnetosheath jets are localized regions of plasma that move faster towards the Earth than the surrounding magnetosheath plasma. Due to their high velocities, they can cause indentations when colliding into the magnetopause and trigger processes such as magnetic reconnection and magnetopause surface waves. We statistically study the occurrence of these jets in the subsolar magnetosheath using measurements from the five Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft and OMNI solar wind data from 2008 to 2011. We present the observations in the B-IMF-v(SW) plane and study the spatial distribution of jets during different interplanetary magnetic field (IMF) orientations. Jets occur downstream of the quasi-parallel bow shock approximately 9 times as often as downstream of the quasi-perpendicular shock, suggesting that foreshock processes are responsible for most jets. For an oblique IMF, with 30-60 degrees cone angle, the occurrence increases monotonically from the quasi-perpendicular side to the quasi-parallel side. This study offers predictability for the numbers, locations, and magnetopause impact rates of jets observed during different IMF orientations, allowing us to better forecast the formation of these jets and their impact on the magnetosphere.